Mangrove Forest Preservation for Environmental Sustainability and Community Welfare Improvement in Suwung Kauh Village Denpasar : An International Community Service Program - Yogiswara Winatha, I Gede Mahatma; Swetasoma, Cokorda Gede; Sumertajaya, I Ketut Satria Wiradharma; Dewi, Kadek Ary Purnama; Suryawan, Tjokorda Gde Agung Wijaya Kesuma (Jurnal Pengabdian UNDIKMA, 2023)
This community service program aims to improve the preservation of mangrove forests by replanting mangrove seedlings to replace old damaged trees and expand the mangrove ecosystems. In addition, coastal cleaning activities were also carried out to reduce plastic waste that pollutes mangrove forest areas in Suwung Kauh Village, South Denpasar. By using a Participatory Action Research (PAR) approach method oriented towards community empowerment, the implementation of community service was carried out by a team of the Faculty of Law and the Faculty of Economics and Business, Ngurah Rai University, in collaboration with Canberra University and KUB Simbar Segara. The evaluation was carried out by the managing team through direct interaction between the interviewer and the respondent using interview and observation techniques for the achievement values of the results of the implementation of community service activities and was analyzed descriptively. The results of the service program succeeded in reducing plastic waste around the area and increasing the area of mangrove areas by planting new seedlings.Â 